Energy-Sector Workforce Development in Southwestern Pennsylvania Aligning Education and Training with Innovation and Needed Skills - Gonzalez, Gabriella C. (RAND Corporation, 2014)
This report documents key technological innovations in the energy sector; identifies best practices of educational and training programs that have successfully responded to evolving labor markets in other sectors; analyzes four case-study energy-sector education and training programs in southwestern Pennsylvania; and provides recommendations for the energy-sector education and training system in the region.